Analisi Implementasi Electronic Commerce Sebagi Media Marketing Usaha Mebel - Suyono Suyono (Dinar Islamic Review, 2022)
In this modern era, the development of the furniture business is growing rapidly with the development of internet technology which makes business competition even tougher. The supporting tool needed in this business is e-commerce. Where e-commerce is a business that involves producers, consumers, service providers and intermediaries using internet technology. The purpose of this research is to utilize the internet to increase sales and increase market share by implementing an android application-based online store at the Muji Mebel store. Research methods include data collection methods and systems development methods. At the data collection stage, the author went directly to the location of the research object and collected information about Muji Mebel Performance, then saw how the information was published. Meanwhile, at the system development stage, the authors use the waterfall model, where the waterfall method has 5 stages, namely post-analysis, system design, implementation, system testing and maintenance. The author concludes that with technology that continues to develop and intense competition in the business world, Muji Mebel is taking steps to create e-commerce applications to facilitate sales and marketing.